KEINDAHAN PENGALAMAN PADANG GURUN DRUPADI - Rahno Triyogo (Institut Seni Indonesia Surakarta, 2009)
This article aims at describing a leading figure’s suffering responded as blessing. The result of the analysis shows that the failure in overcoming various problems of life is determined by a person’s attitude toward the problems themselves. The various problems of life are called the desert of life. Submission to God’s will brings in blessing. People with divine blessing show kindness in accordance with God’s disposition. Key words : desert, submission, blessing